(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
INTRODUCTION: Breast cancer is the most common cancer in worldwide between age of 20-59 years females. It is responsible for 15% of total deaths due to cancers. FNAC is one of the important components of ‘triple approach’, which has been widely accepted for the preoperative diagnosis of breast lesions. AIM: To establish utility and effectiveness in diagnosis of breast lesion by FNAC and find the incidence of breast cancer in palpable lump in different age groups. MATERIAL AND METHODS: In this study100 cases of breast lump referred by the Surgery Department of LG Hospital was included in study period fromAugust2016toOctober2018. RESULT: Out of the 100 cases, in 99 cases the aspirates were adequate for interpretation. Out of 100, 90cases underwent a biopsy and could be correlated histopathologically. According to NHSBSP, there was 1 case in C1 category,64 cases in C2 category, 3 cases in C3 category, 2 cases in C4 category and 30casesin C5 category. CONCLUSION: The present study categorized by NHSBSP criteria conclude 100% confirmation in C4 and C5 category in age group above 40 years showing malignancy by histopathology. The overall sensitivity in the study was 83.33%, specificity was 100%, positive predictive value in disease was 100% and the false negative percentage was 16.66%. FNAC is an accurate and reliable preoperative diagnostic tool for breast lesions.